COPYRIGHT LAW ENFORCEMENT AGAINST SOFTWARE PIRACY VIOLATIONS FOR COMMERCIAL PURPOSES - Ramadhanty, Venta Ananda; Astutik, Sri; Prawesthi, Wahyu; Handayati, Nur (Jurnal Ilmiah Advokasi, 2025)
Copyright infringement in the form of software piracy has various modes that lead to crime. This research aims to analyze forms of copyright infringement, enforcement and protection of software copyright based on the Copyright Law. This research used normative juridical method with statute approach and conceptual approach. The research results show that piracy of computer software is a violation of copyright, because in economic use/commercial use of computer software, written permission is required in the form of license. Person who feels aggrieved by the occurrence of this violation can file a lawsuit with the Commercial Court. Law enforcement is carried out by the government, police and judicial institute. Perpetrators of illegal computer software license can be subject to criminal sanctions, especially in Article 112 and 113 of the Copyright Law. Apart from that, there are several alternative non-litigation dispute resolution methods. Preventive protection is carried out by the government in terms of supervising software creation and collaborating with various parties. Repressive measures include fines, imprisonment and additional penalties.Keywords: protection; enforcement; piracy; software, copyright